الاشتغال الدلالي للعلامة في الدرس السيميولوجي - حورية, كريدات (جامعة الوادي - University of Eloued, 2021)
تسعى ورقتنا البحثية إلى ضبط التصور السيميائي للعلامة و فهمها من حيث التأصيل لها و التحول المنهجي الذي مرت به بدءً من اللساني "دي سوسير" الذي ربط دراسة حياة العلامات بالحياة الاجتماعية، والفيلسوف "بيرس" والذي أسس للعلامة من حيث علاقة المنطق باللغة. و قد شكل الطرح المنهجي للعلامة السوسيرية والعلامة البيرسية بوابة لطروحات جديدة في فهم العلامة وتوسيع مفاهيمها اللّسانية والسيميائية، وقد فُتح المجال إلى من جاء بعدهما في البحث السيميولوجي عن حقيقة كل ما ينطق به الانسان سواء بالعبارة اللّفظية أو الاشارة غير اللّفظية، وقد أولى الحقل اللساني و السيميائي اهتماما كبيرا للعلامة السيميولوجية من حيث الاشتغال الدلائلي . ومن أهم الدارسين اللغويين و السيميائين "هيلمسلف" في تصوره الجديد للسيميائيات وقدّم نظريته التي تقوم على الطرح الجديد للمادة و الشكل، و المضمون و التعبير. أمّا رولان بارث قد تمثل منظوره السيميولوجي في إعادة تشكيل اشتغال الأنظمة الدلالية غير اللسانية،وقَلب الاقتراح السوسيري، معتبرا السيميولوجيا جزء من اللسانيات. فالعلامة تتحقق في السيرورة اللغوية و لايمكن فصلها عن اللغة . Abstract: Our research paper seeks to determine the semiotic perception of the sign and to understand it in terms of its rooting and the methodological transformation that it underwent according to the linguist de Saussure, who linked the study of signs’life to social life, and the philosopher Peirce, who theorized aboutthe sign in terms of the relationship between logic and language. As a matter of fact, the methodical presentation of the sign put forward by the Sociologistde Saussure and thephilosopherPeirceformed a gateway to new approaches in understanding the sign and expanding its linguistic and semiotic concepts. The field was, then, opened to those who came after them in the semiological search for the truth behind everything that a person utters, whether by verbal phrase or non-verbal signal.Indeed, the linguistic and semiotic fields gave a great attention to the semiological sign in terms of indicative process. Notably, one of the most important scholars of linguistics and semiotics,"Hjelmslev",has presented,in his new conception of semiotics, atheory based on a new way of approaching matter, form, content and expression.As for Roland Barth, his semiological perspective may be represented in reconfiguring the functioning of non-linguistic semantic systems, and inverting de Saussure’sclaim, considering semiology as part of linguistics. Thus, the sign is realized in the linguistic process and cannot be separated from the language.
مقال
Keywords: لعلامة السيميائية ، العلامة اللسانية ،السيميائيات، السيميولوجيا الدال ، المدلول ، الدليل، الاشتغال الدلالي; The Semiotic sign, the linguistic sign, semiotics, semiology, the signifier and the signified, the evidence, the semantic process